Business interest representation and European Commission fora: A game theoretic investigation - Andreas Broscheid; David Coen (Max Planck Institute for the Study of Societies, 2002)
The relationship between business and the EU institutions has evolved from its corporatist origins into a complex elite pluralist arrangement centered around industrial fora and policy committees. We view the growth of forum politics as the direct consequence of the unprecedented boom in economic and public interest lobbying in the early 1990s: While the increase in European interest representation provided greater legitimacy for the European integration program, it put a strain on the existing open pluralist European business-government relationship. One of the European Commission's (EC) informal solutions was to create restricted-entry policy fora and select committees, which it hoped would provide fast and reliable decisionmaking. Employing a formal model of industrial fora and committees, we specify the mechanisms that we believe caused the establishment of the current elite pluralist system of interest representation in the EU. We argue that in the process of establishing selective-entry fora for interest representation, the European Commission acted not only as policy entrepreneur, but also as a political entrepreneur, fostering collective action. – – Die Beziehungen zwischen Wirtschaft und EU-Institutionen hat sich aus korporatistischen Anfängen zu einem komplexen Arrangement elitenpluralistischer Strukturen entwickelt, in dessen Mittelpunkt Industrieforen und Policy-Komittees stehen. Wir analysieren die wachsende Bedeutung dieser Forum Politics als direkte Folge des (wirtschaftlichen und zivilgesellschaftlichen) Lobbying-Booms der frühen 90er-Jahre. Obschon die vermehrte europäische Interessenvertretung die Legitimtät des europäischen Integrationsprogramms erhöhte, setzte sie zugleich das bestehende System offener pluralistischer Beziehungen zwischen Wirtschaft und europäischen Institutionen unter Druck. Als eine informelle Lösung dieses Problems etablierte die Europäische Kommission nichtständige Policy-Fora und Ausschüsse, deren Zugang sie kontrollierte. Mit Hilfe eines formalen Modells identifizieren wir die Mechanismen, die unseres Erachtens zu der Entwicklung des gegenwärtigen elitenpluralistischen Systems der EU-Interessenvertretung geführt haben. Wir argumentieren, dass die Europäische Kommission mit der Einrichtung zugangsbeschränkter Fora zur Interessenvertretung nicht nur as 'policy entrepreneur' tätig wurde, sondern auch als 'political entrepreneur' kollektives Handeln von Interessenvertretern förderte.
Keywords: 300